Diplomasi Budaya Jepang Melalui Strategi Cool Japan Di Indonesia - Azhari, Dinda Puan Maharani; Surya, Aelina (Universitas Komputer Indonesia, 2024)
The Cool Japan strategy is a strategy or initiative undertaken by the Japanese government to promote Japan through its culture and creative industries, to enhance the positive image and brand of Japan in the eyes of the international community. Cultural diplomacy by Japanese in Indonesia through the Cool Japan strategy is an effort by Japan to support national interests, by promoting the characteristics and uniqueness of the Japanese through culture. This research aims to analyze Japan's cultural diplomacy efforts through the Cool Japan strategy in Indonesia to support Japan in achieving their national interests. The method used in this research is descriptive qualitative, where in the process of collecting data obtained through primary data, which is interviews, and through secondary data, through previous scientific research. The result of the research is that Japanese cultural diplomacy through the Cool Japan strategy has succeeded in presenting Japanese culture in Indonesia, so that it can support Japan in their national interests, namely nation branding, as well as increasing the value of creative industry exports, and promoting Japanese culture. In addition, the Cool Japan strategy has also played a role in strengthening friendly relations between Japan and Indonesia through cultural exchanges. Keywords — Cool Japan strategy, culture, diplomacy, Indonesia, Japanese, national interest